Influence of Anxiety on Executive Functioning in Patients with Idiopathic Parkinson's Disease without Dementia (2024)
To study the relationship between anxiety and executive functions in patients with Idiopathic Parkinson's Disease without dementia (IPD without dementia) stages I and II of Hoehn and Yahr. Anxiety is the second most frequent alteration in IPD without Dementia, with important repercussions on neurocognitive functioning and quality of life.